ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL SEBELUM DAN SELAMA KRISIS EKONOMI PADA PERUSAHAAN NON FINANSIAL YANG GO PUBLIK DIINDONESIA - Setiyanti, Sri Wiranti (JURNAL STIE SEMARANG, 2009)
The decision  about capital structure  is crucial for financial  managers that related  with company's  survival.  The fulfillment  of capital requirement can  be obtained  from  internal  and  external  sources.  Financial  managers must be able to fulfill capital requirement and use it efficiently. To determine capital structure there are several factors that influences financial managers to  make  decision  about capital  structure,  such as  : sales stability,  assets structure,  growth  rate,  profitability,  taxes,  control,  management   attitude, creditor attitude, market conditions and company's internal conditions. This study examines the effects of assets structure, growth rate, taxes, expense, profitability, devidend payout ratio, return on investment and return onequity  variable  on non-financial  company's  structure,  both partially  and simultaneousiy  and to test whether  the effects of these variables  differs  in periods before and during economics  crisis. The population in this study is non-financial  company's  listed  in Jakarta  Stock Exchange  until 1993. The sample  determined  by purposive  sampling  methods  and based  on criteria 74 companies  are obtained as a samle. Study data is secondary in nature that obtained  from  Indonesian  capital  Market Directory  (ICMD).  Data was analyzed by multiple regresions. The   results    show   that   both   partially   and   simultaneously,    all independent  variables  in this study are positively and significantly influence capital   structure   in  period   before   economics   crisis.   In  periods   during economics  crisis,  partially  only devidend  payout  ratio  that  negatively  and inSignificantly  influences  capital  structure,  but  Simultaneously  all independent  variables  significantly  influence  capital  structure.  Economics crisis  also  differentiate  the  influence  from  all  independent  variables  on capital structure between periods before and during economic crisis.